Cardiorespiratory and metabolic answer with microemulsion and lipid emulsion of propofol in cats Respostas cardiorrespiratória e metabólica do propofol nas formulações em emulsão lipídica ou microemulsão em gatas - Tamanho R.B.* (2013)
The aim of the present study was to evaluate the cardiorespiratory and metabolic effects from lipid emulsion and microemulsion of propofol in cats. Twelve healthy adult cats were included, and divided into two groups: microemulsion group (MICRO, n=6) and lipid emulsion (EMU, n=6), where they received propofol in the respective formulation, in a dose sufficient for intubation. The animals were then intubated and provided with 100% oxygen through a non-rebreathing circuit. Immediately after, the infusion of propofol was initiated (0.3mg kg-1 min-1) and maintained for 90 minutes. The dose required for induction was 9.5±1.3mg kg-1 and 10±1mg kg-1 in MICRO and EMU, respectively. The SAP, MAP, DAP and pH values were lower in all moments in EMU when compared to MICRO; the RR in EMU was lower from T30 to T75 in comparison to MICRO. The paCO2 was greater in the EMU from T15 to T90. The times to extubation, sternal recumbency, ambulation and total recovery were 40.6±30.7, 91±37.5, 134.5±54.5 and 169.1±55.4 minutes in MICRO and 68.8±37.3, 133.3±85.3, 171.3±77.1 and 233.1±60.6 minutes in EMU, respectively. There was an increase of the enzyme alanine aminotransferase from 12 to 72 hours in EMU and in MICRO from 48 to 72 hours. The propofol in microemulsion presents clinical characteristics of induction and maintenance, and metabolic effects similar to the formulation in lipid emulsion. The microemulsion formulation provides a better cardiovascular and respiratory stability for induction and continuous infusion in healthy cats.